Late Malignancy after 26 Years of Evolution on an Untreated Perianal Fistula - Lucian Sorin ANDREI; Adriana Corina ANDREI; Alexandru MICU; Radu Sorin POPISTEANU; Mona DUMBRAVA (Modern Medicine)
Squamous cell carcinoma and basal cell carcinoma are two types of neoplasms that rarely affect the perianal region, and their etiology is still a matter for debate. We present the case of a 75 year old patient with a 26 year history of perianal fistula, who presents with purulent and fecal perianal discharge and swelling at this level. Physical examination and anoscopy detected low transsphincteric fistula. The biopsy revealed the diagnosis of squamous cell carcinoma, for which a local excision was performed followed by adjuvant radiotherapy. Two years after this event, the patient presented with another perianal lession, which according to the histopathological result was a basal cell carcinoma; local excision was the only treatment performed for this malignancy.